Degenerative gluteal tears associated with hip arthroplasty - Dani Gaillard-Campbell; Thomas Gross (BMC Musculoskeletal Disorders)
Abstract Background Unrepaired chronic abductor tears may be a cause of residual pain and weakness after hip arthroplasty, but the current incidence is unclear. Methods From 1994 to 2009, the senior surgeon performed 1628 hip resurfacing and 864 total hip arthroplasties without identifying any gluteal tears. We recognized our first case of concomitant abductor tear during a hip resurfacing procedure in April 2009. After this, we began following a protocol to identify and repair abductor tears in the next 5601 consecutive primary hip arthroplasties (5429 hip resurfacings and 172 total hips). Results Women over 60 were the highest-risk group for abductor tear, with a 3.6% rate of tears identified. All tears were repaired. We found no differences in mean HHS and VAS pain score in patients with repair gluteal tears versus a control group of cases without a tear. Patients without a tear had higher postoperative UCLA activity scores at 2 years postoperative. The majority (98.1%) of hip arthroplasty patients with a gluteal tear repair at time of surgery presented with 4 or 5 abductor strength at their 2-year postoperative physical exam. Of our abductor tear cohort, 70.3% had no limp and 21.9% had a slight limp at 2 years postoperative. Conclusions In a large group of hip arthroplasty cases (n = 4507), we identified gluteal tears in 3.6% of women and 1.0% of men. All reported clinical outcomes (excluding mean HHS) in our cohort of hip arthroplasty patients did not differ significantly between cases without abductor tears and those that had gluteal repair at time of surgery. These results suggest abductor tears may be repaired at time of hip arthroplasty surgery without forgoing desirable functional outcomes. Level of evidence Level 3 Retrospective Cohort Study.